2023
DOI: 10.1039/d3ma00054k
|View full text |Cite
|
Sign up to set email alerts
|

Ni(ii) and Zn(ii)-metallogel-based anti-bacterial scaffolds for fabricating light-responsive junction-type semiconducting diodes with non-ohmic conduction mechanism

Abstract: Metal incorporation into the gelator offers an effective strategy to fabricate soft scaffolds with advanced functionality. Herein, we report self-assembly directed two supramolecular metallogels of sebacic acid with Ni(II) and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 91 publications
(115 reference statements)
0
13
0
Order By: Relevance
“…In general, metal ions exhibit diverse antimicrobial activities, and these properties have been recognized throughout the history of medicine and healthcare. In this study, the metallogels showed antimicrobial activity against both Gram-positive and Gram-negative bacteria . However, the effectiveness of antimicrobial activity varies between metallogels. , In the present work, it was found that Ni­(II)-metallogel showed slight antimicrobial efficiency compared to Co­(II)-metallogel and Zn­(II)-metallogel of azelaic acid used as the low molecular weight organic gelator. These differences in the antimicrobial activity of the metallogels could be due to the differences in the bioavailability of the metal ions during gel-formation.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…In general, metal ions exhibit diverse antimicrobial activities, and these properties have been recognized throughout the history of medicine and healthcare. In this study, the metallogels showed antimicrobial activity against both Gram-positive and Gram-negative bacteria . However, the effectiveness of antimicrobial activity varies between metallogels. , In the present work, it was found that Ni­(II)-metallogel showed slight antimicrobial efficiency compared to Co­(II)-metallogel and Zn­(II)-metallogel of azelaic acid used as the low molecular weight organic gelator. These differences in the antimicrobial activity of the metallogels could be due to the differences in the bioavailability of the metal ions during gel-formation.…”
Section: Resultsmentioning
confidence: 53%
“…70 However, the effectiveness of antimicrobial activity varies between metallogels. 36,45 In the present work, it was found that Ni(II)-metallogel showed slight antimicrobial efficiency compared to Co(II)-metallogel and Zn(II)-metallogel of azelaic acid used as the low molecular weight organic gelator. These differences in the antimicrobial activity of the metallogels could be due to the differences in the bioavailability of the metal ions during gel-formation.…”
Section: Rheological Experimental Analysis Of Metallogelsmentioning
confidence: 56%
See 1 more Smart Citation
“…Scientists are very much fascinated about LMOGs not solely for the purpose of academic level but also because of their enormous implementations ranging from the academic to industrial domains, such as chemical sensing, catalytic reaction, organic electronics, , cosmetic industry, conservation of arts, and water purification, and for biological utilities like drug transportation, cellular supports, tissue engineering application, and so on . Apart from these applications, we observe some extra functional properties like redox activity, conductivity, , optical properties, magnetic features, nano science and nano electronics, and proton conductivity, , which are exhibited by the metallogels.…”
Section: Introductionmentioning
confidence: 97%
“…The incorporation of different functional groups in gelator molecules such as hydroxyl, , carboxylic, phosphate, along with nitrogen, oxygen, and sulfur containing compounds leads to diverse properties of metallogels. It offers potent functionality in different fields of biochemistry, catalysis, antipathogenic activity, medical diagnostics, drug delivery, cell culturing, chemo sensors, tissue engineering, biomineralization, electrochemical devices, nonlinear optics, , lithography, pollutant removal, etc. Besides, the metallogels are also used in phase partition, catalytic reactions of organic compounds, oil spill remedy, , water treatment, , etc.…”
Section: Introductionmentioning
confidence: 99%